B-type natriuretic peptide informativeness in myocardial revascularization with cardio-pulmonary bypass - I. A. Kozlov; L. A. Krichevskiy; V. Yu. Rybakov (Вестник анестезиологии и реаниматологии, 2024)
The objective was to study the dynamics of B-type natriuretic peptide (BNP) and its relationship with hemodynamic parameters during on-pump coronary artery bypass grafting (CABG), and to evaluate the informativeness of the biomarker as a predictor of myocardial dysfunction.Materials and methods. The study involved 127 patients aged 59 [54–66.75] years with ischemic heart disease who underwent CABG. The BNP blood level was determined in the operating room at stages: I – before surgery (BNP1 ), II – at the end of surgery (BNP2 ). Hemodynamic parameters were analyzed at the same stages. Correlation analysis, logistic regression with the calculation of the odds ratio (OR) and 95% confidence interval (95% CI) and ROC analysis with the calculation of the area under the ROC curve (AUC) were used.Results. BNP1 blood level was 49 [25.6–91.6], BNP2 – 90 [47.8–140.2] pg/ml (p < 0.0001). BNP1 correlated with central venous pressure (CVP) at stage I (rho = 0.212; p = 0.017) and with pulmonary artery wedge pressure (PAWP) at stage II (rho = 0.204; p = 0.045). BNP2 correlated with PAWP at stage II (rho = 0.204; p = 0.045). BNP1 > 52.1 pg/ml was the predictor of ICU length of stay > 24 hours (OR 1.0290, 95% CI 1.0154– 1.0427, p < 0.0001, AUC 0.775), BNP1 > 71 pg/ml was the predictor of inotropic index > 5 c. u. (OR 1.0076, 95% CI 1.0015–1.0138, p = 0.014, AUC 0.705) and BNP1 > 90.8 pg/ml was the predictor of vasoactive inotropic index > 10 c. u. (OR 1.0070, 95% CI 1.0014–1.0126, p = 0.013, AUC 0.727). BNP2 > 67.5 pg/ml was the predictor of ICU length of stay > 24 hours (OR 1.0179, 95% CI 1.0073–1.0287, p < 0.0009, AUC 0.763), BNP2 > 94.3 pg/ml was the predictor of inotropic index > 5 c. u. (OR 1.0063, 95% CI 1.0010–1.0117, p = 0.020, AUC 0.713), BNP2 > 144 pg/ml was the predictor of intra-aortic balloon pumping (OR 1.0037, 95% CI 1 .0000–1.0074, p = 0.048, AUC 0.854), BNP2 > 159 pg/ml was the predictor of vasoactive inotropic index > 10 c. u. (OR 1.0072, 95% CI 1.0006–1.0139, p = 0.033, AUC 0.729) and BNP2 > 161 pg/ml was the predictor of early mortality in the ICU (OR 1.0040, 95% CI 1, 0000-1.0080, p = 0.049, AUC 0.845). Conclusion. In 78.7% of patients undergoing on-pump CABG, BNP blood level does not exceed the upper limit of normal; by the end of surgery, the biomarker level increases by 32.9 [17.7–62.0] pg/ml. Before and at the end of surgery, BNP values are weakly correlated with CVP and PAWP and do not correlate with other hemodynamic parameters. Before surgery, BNP blood level in the range of 52.1–90.8 pg/ml are predictors of ICU stay > 24 hours (AUC 0.775), inotropic scale > 5 (AUC 0.705) and vasoactive-inotropic scale > 10 c. u. (AUC 0.727). At the end of surgery, BNP > 67.5 pg/ml is associated with an ICU stay > 24 hours (AUC 0.763), and BNP > 90.4 pg/ml is associated with inotropic scale > 5 c. u. (AUC 0.713). The BNP, increased to 144.0–161.0 pg/ml, indicates severe myocardial dysfunction, including hemodynamic support with intra-aortic balloon pumping (AUC 0.854), vasoactive-inotropic scale > 10 c. u. (AUC 0.729) and the risk of early mortality in the ICU (AUC 0.845).